Prey Preferences of the Jaguar Panthera onca Reflect the Post-Pleistocene Demise of Large Prey - Hayward, Matt W.; Kamler, Jan F.; Montgomery, Robert A.; Newlove, Anna; Rostro-García, Susana; Sales, Lilian P.; Van Valkenburgh, Blaire (Frontiers in Ecology and Evolution, 2016)
Documenting the impacts of the Pleistocene megafaunal extinctions on predator-prey interactions is a challenge because of the incomplete fossil record and depauperate extant community structure. We used a comparative ecological approach to investigate whether the existing prey preference patterns of jaguars Panthera onca were potentially affected by the Pleistocene extinctions in the Americas compared with large felids in Africa and Asia. We reviewed the literature and found 25 studies reporting 3214 jaguar kills recorded throughout the species’ distribution. We found that jaguars significantly preferred capybara Hydrochaeris hydrochaeris and giant anteater Myrmecophaga tridactyla, and avoided agoutis, carnivorans, primates, black-eared opossum Didelphis marsupialis and tapirs. Generalised linear models showed that jaguars select prey primarily based on socio-ecological and behavioural traits (abundance and herd size), rather than morphological characteristics (body size). Nonetheless, their accessible prey weight range was 6-60 kg, preferred prey weight range was 45-85 kg, and mean mass of significantly preferred prey was 32 ± 13 kg leading to a predator to prey body mass ratio of 1:0.53, which is much less than that of other solitary felids. Compared with other large, solitary felids, jaguars have an unusual predator to prey body mass ratio, show limited effect of prey morphology as a driver of prey selection, lack evidence of optimal foraging beyond their preferred prey, and an absence of preferentially hunting on Cetartiodactyla herbivores. These features, coupled with the reduction in jaguar body mass since the Pleistocene, suggest that the loss of larger potential prey items within the preferred and accessible weight ranges at the end-Pleistocene still affects jaguar predatory behaviour. It may be that jaguars survived this mass extinction event by preferentially preying on relatively small species.